2017
DOI: 10.1038/srep41254
|View full text |Cite
|
Sign up to set email alerts
|

Costunolide and dehydrocostuslactone combination treatment inhibit breast cancer by inducing cell cycle arrest and apoptosis through c-Myc/p53 and AKT/14-3-3 pathway

Abstract: Our previous studies demonstrated that volatile oil from saussurea lappa root (VOSL), rich in two natural sesquiterpene lactones, costunolide (Cos) and dehydrocostuslactone (Dehy), exerts better anti-breast cancer efficacy and lower side effects than Cos or Dehy alone in vivo, however, their anti-cancer molecular mechanisms were still unknown. In this study, we investigated the underlying mechanisms of Cos and Dehy combination treatment (CD) on breast cancer cells through proteomics technology coupled with Wes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(39 citation statements)
references
References 59 publications
2
37
0
Order By: Relevance
“…DHC was found to induce mitochondrial intrinsic apoptosis with enhanced pro-apoptotic effects of DOX in both cell lines. DHC was shown to induce apoptosis in liver [ 9 , 10 ], breast [ 11 , 12 ], leukemia [ 13 ], prostate [ 14 ], ovary [ 15 ], colon [ 16 ], and bladder cancer [ 17 ]. DHC caused reduction in HIF-1α levels in A549 and H460 cells followed by suppression of the levels of Akt and pAkt, GSK-3β and pGSK-3β, and mTOR and p-mTOR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DHC was found to induce mitochondrial intrinsic apoptosis with enhanced pro-apoptotic effects of DOX in both cell lines. DHC was shown to induce apoptosis in liver [ 9 , 10 ], breast [ 11 , 12 ], leukemia [ 13 ], prostate [ 14 ], ovary [ 15 ], colon [ 16 ], and bladder cancer [ 17 ]. DHC caused reduction in HIF-1α levels in A549 and H460 cells followed by suppression of the levels of Akt and pAkt, GSK-3β and pGSK-3β, and mTOR and p-mTOR.…”
Section: Discussionmentioning
confidence: 99%
“…Dehydrocostus lactone (DHC) is a sesquiterpene lactone isolated from Chinese herbs like Saussurea lappa and Laurus nobilis . DHC has been used to treat various diseases, including prevention of various types of cancers, such as liver cancer [ 9 , 10 ], breast cancer [ 11 , 12 ], leukemias [ 13 ], prostatic cancer [ 14 ], ovarian cancer [ 15 ], colorectal cancer [ 16 ], and bladder cancer [ 17 ]. DHC mediates anti-cancer effects by interacting mechanisms like inhibition of telomerase activity, induction of cellular apoptosis pathways (mitochondrial intrinsic and death-receptor dependent extrinsic), induced endoplasmic reticulum (ER) stress [ 18 ], and limiting migration-invasion and metastasis [ 8 , 16 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Due to various biotic and therapeutic applications of active ingredients, herbal medicine is gaining importance these days and is foundation for revolution in drug discovery. Bioactive agents obtained from various herbal drugs are irreplaceable in the management of many intractable diseases and one such drug is Saussurea lappa (Qust), one of the best-known species of Asteraceae family, is a tall perennial herb possessing antihepatitis B [1,2] antioxidant [3,4] hepatoprotective [5] and anticancerous [6,7] activity. Morphologically its stem is stout and fibrous, root is long, firm with characteristics odor, leaves are lobate and stalked, flowers are dark purple, stalkless and are arranged at periphery.…”
Section: Introductionmentioning
confidence: 99%
“…Costunolide, a sesquiterpene lactone isolated from the roots of Inula helenium L , exerts a wide spectrum of biological effects, including antimicrobial, anti‐inflammatory, and anti‐proliferative effects, on several cancer cell lines (Y. K. Choi et al, ; Peng et al, ). Many previous studies have reported that costunolide can inhibit cancer cell growth by inducing caspase‐dependent apoptosis and/or cell cycle arrest (Butturini et al, ; J. H. Choi & Lee, ).…”
Section: Introductionmentioning
confidence: 99%
“…Costunolide, a sesquiterpene lactone isolated from the roots of Inula helenium L, exerts a wide spectrum of biological effects, including antimicrobial, anti-inflammatory, and anti-proliferative effects, on Abbreviations: BCA, bicinchoninic acid; RIPA, radio immunoprecipitation assay; RPMI, roswell park memorial institute; PVDF, polyvinylidene fluoride; SDS, sodium dodecyl sulfate; V-FITC, V-fluorescein isothiocyanate † Hong Cai and Xiaolin He contributed equally to this work. several cancer cell lines (Y. K. Choi et al, 2012;Peng et al, 2017).…”
Section: Introductionmentioning
confidence: 99%